Analisis Sistem Perbandingan Kekuasaan Kehakiman Antara Negara Indonesia Dengan Negara Prancis - Diki Rahmawan; Fatur Faturohman (Universitas Kuningan, 2024)
This research aims to determine the judicial power between Indonesia and France. From the perspective of the legal system, the two countries have differences. So, there are also differences in terms of the system of judicial power implemented by the Indonesian state and the French state. The scope of the research explains the judicial power of the Supreme Court and the Constitutional Court in Indonesia and France, and the principles of judicial power between Indonesia and France. The research method used in this research is a normative legal research method, namely research that is viewed from the perspective of statutory regulations, which are used as a benchmark for human behavior. The research results show differences between the judicial power systems between Indonesia and France. The main factor that differentiates the judicial system between the two countries is that the legal system applied by the two countries is different, where Indonesia applies a mixed legal system, while France applies a mixed legal system. So that. The systems of judicial power in the two countries have differences, including regarding the principles of judicial power between Indonesia and France.